Cultural Representation and Women's Issues in the Film Wadjda: A Feminist Perspective - Nabila, Choirunnisa; Yurisa, Penny Respati (Jurusan Pendidikan Bahasa Arab IAIN Ponorogo, 2025)
The film “Wadjda” is a distinctive work that provides insight into the lives of Saudi Arabian women, particularly within the context of a society deeply entrenched in patriarchal norms. The character of Wadjda symbolizes women's empowerment and embodies the ongoing struggle against inequality, highlighting the daily challenges women face in confronting gender discrimination. This study aims to analyze the representation of culture and women's issues, with a particular emphasis on the theme of gender equality as presented in “Wadjda”. Employing a qualitative descriptive approach, this research primarily focuses on the film “Wadjda”, directed by Haifaa Al-Mansour in 2012, and is analyzed through the lens of liberal feminist theory. Data collection utilizes the listen-read-record technique for the research object, while data analysis incorporates data reduction, data presentation, and verification methods. The findings reveal seven key issues related to gender inequality: the accessibility of freedom primarily for men, limited access for women due to unjust social norms, public harassment of women, women's aspirations for freedom and equality, the imbalance of power affecting the treatment of women, patriarchal traditions that restrict women's autonomy, and inequalities in marriage. This research is anticipated to contribute to the discourse on social change towards gender equality, as well as provide a deeper understanding of feminism through media representations, particularly in illustrating women's struggles within a culture that constrains them. Abstrak Film Wadjda merupakan karya yang unik menawarkan perspektif tentang kehidupan perempuan Arab Saudi, terutama dalam konteks masyarakat yang kental dengan norma patriarkal. Karakter Wadjda menjadi simbol pemberdayaan perempuan yang berjuang untuk melawan ketidaksetaraan, serta menggambarkan perjuangan sehari-hari perempuan dalam menghadapi diskriminasi gender. Penelitian ini bertujuan menganalisis representasi budaya dan isu perempuan dengan fokus pada kesetaraan gender yang diangkat dalam film Wadjda. Penelitian ini menggunakan pendekatan deskriptif kualitatif, dengan sumber utama penelitian adalah film Wadjda yang disutradai oleh Haifaa Al-Mansour pada tahun 2012 dan dianalisis dengan pendekatan teori feminisme liberal. Metode pengumpulan data menggunakan teknik dengar-baca-rekam terhadap objek penelitian. Sedangkan analisis data menggunakan reduksi data, penyajian data dan verifikasi. Hasil penelitian menunjukkan ada tujuh isu utama terkait ketidaksetaraan gender: kebebasan yang lebih mudah diakses oleh laki-laki, kurangnya akses perempuan akibat aturan sosial yang tidak adil, pelecehan publik terhadap perempuan, keinginan perempuan untuk kebebaasan dan kesetaraan, ketidaksimbangan kekuasaan yang mempengaruhi perlakuan terhadap perempuan, tradisi patriarkal yang membatasi otonomi perempuan, serta ketidaksetaraan dalam pernikahan. Penelitian ini diharapkan dapat memeberikan kontribusi pada diskusi tentang perubahan sosial menuju kesetaraan gender, serta memberikan wawasan lebih dalam studi feminisme melalui media, khususnya dalam menggambarkan perjuangan perempuan dalam budaya yang membatasi mereka.